Types of Slang Found in Raya and the Last Dragon Movie Series 2021 by Walt Disney - Pande Wayan Tonjaya Putra; Ida Bagus Gde Nova Winarta (EDULIA: English Education, Linguistic and Art Journal, 2022)
The objective of this study is to know what types of slang found in Raya and The Last Dragon movie. As said before, the data source for this paper is a movie entitled Raya an The Last Dragon. The data was analyzed using descriptive qualitative method use theory from Allan and Burridge (2006) who divided slang into five types, that are fresh and creative, flippant, imitative, acronym, and clipping.After doing the observation and collecting the data, researcher found 8 data. Moreover, after the analyzation researcher can conclude that the data that found can classified into four types of slang from Allan and Burridge that are 3 data for fresh and creative, 2 data for imitative, 1 data for flippant and 2 data for clipping, researcher do not found the data that can classified as acronym. Keywords: movie, Raya and the Last Dragon, slang, linguistic, sociolinguistic.